(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This study critically evaluates the translations of poetic figures in Kutadgu Bilig (Wisdom of Royal Glory), a foundational work of Turkic-Islamic literature, with a particular emphasis on the manner in which these figures are captured in the English and Russian translations. The study looks at the cultural and linguistic elements that affect how readers understand the text, using reception theory as a guide (Jauss, 1982; Iser, 1978). It looks at how the translation methods used by Robert Dankoff (English, 1983) and Sergei Ivanov (Russian, 1971) are different and how these methods affect how readers perceive and enjoy metaphors, parallelism, symbolism, allegory, and personification. The results indicate that Russian translations are more faithful to the original since they are closer to the culture, while English translations focus on being clear and easy to understand rather than being rich in style. The article suggests using hybrid translation methods that strike a compromise between being true to the original text and being for readers to understand.